Eco-efficiency and saving by reducing the infectious waste of the Hospital Auxiliar de Suzano - Viriato, Aírton; de Moura, Anísio (O Mundo da Saúde, 2011)
In health sector, an eco-efficient system is the one that achieves high productivity with good quality levels, provides saving of financial resources and has a decreasing scale of waste generation volume. This paper aimed at reducing the volume of infectious waste produced at the Hospital Auxiliar de Suzano; lowering the rate of incinerated waste; lessening the environmental impact effects; enhancing the waste handling and discard conditions in the first-aid and procedure rooms; and diminishing the risk of labor exposure to the products generated by the infectious waste. From June to August 2010, one adopted waste sorting measures to collect the waste produced at the hospital, the organic food and the infectious substances, according to the compliances of the Health Service Waste Management Plan. From adopting these management measures in June 2010, there was a decrease of 40% in the rate of incinerated infectious waste and then a cost reduction.